Bacteriological Study of Wound Infections and Their Antibiogram Pattern at A Tertiary Care Hospital in Suburban Area of Hyderabad - Bhumbla, Upasana; Bandey, Lubna; Ahmad, Safaa Muneer; ., Gyaneshwari (Annals of Pathology and Laboratory Medicine, 2018)
Background: Wound infections can be caused through two major sources: exogenous and endogenous bacteria. The probability of wound infection largely depends on the patient’s systemic host defenses, local wound conditions and microbial burden. Despite modern surgical techniques and the use of antibiotic prophylaxis, Surgical Site Infection (SSI) is one of the most common complications encountered in surgery. SSI places a significant burden on both the patient and health system. SSI is thus a major cause of morbidity, prolonged hospital stays and increased health costs. Methods: Two wound swabs were collected from the wound and from a drop of aspirate, smear was made on clean glass slide and Gram staining was done for direct microscopic examination under oil immersion 100X objective to know various morphological types of bacteria and presence or absence of inflammatory cells. Second swab/drop of aspirate was used for culture by inoculating it on routine media like Blood Agar, Nutrient Agar and MacConkey’s agar, incubated at 37° C for 24 hrs. aerobically. Result: Out of 108 pus samples, 101(88.5%) were culture positive for bacterial growth and no growth was observed in 7(11.4%) cases. Out of 101 bacterial culture positive cases, 96 were nonbacterial and 5 were poly bacterial. Out of 96 bacterial isolates; S. aureus (38/36.6%) was the commonest followed by P. aeruginosa (26/24.7%) Conclusion: The study concludes that variety of aerobic bacteria is responsible for wound infection with predominance of Staphylococcus aureus followed by Pseudomonas aeruginosa.